The Effect Of Crisscross Training And Crossovers Training Using Ladder Drill On Improving Dribbling Ability In Athletes Of Syekh Yusuf Football School - Syamsurahman, Syamsurahman; Nawir, Nukhrawi; Sudiadharma, Sudiadharma; Hudain, Muh. Adnan; Muhammadong, Muhammadong (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study is an experimental study that aims to determine: 1) The effect of crisscross training on improving dribbling skills in Syekh Yusuf football school athletes; 2) The effect of crossovers on improving dribbling skills in Syekh Yusuf football school athletes; and 3) The difference in the effect of Criscross training and Crossovers training on improving dribbling skills in Syekh Yusuf football school athletes. The population in this study were Syekh Yusuf football school athletes with a sample of 20 athletes using random sampling techniques and a group division system using matching ordinal pairing. The research instruments used were descriptive analysis, data normality analysis, homogeneity analysis, and t-test analysis with the help of the SPSS version 21.00 application. The results of the study showed that; (1) There is an influence of Criscross training on increasing dribbling ability in Syekh Yusuf football school athletes, as proven by an increase in speed from an average value of 26.6220 to 16.3340 with an observation value of 19.912 > ttable 2.262 and a significant value of 0.000 < α0.05; (2) There is an influence of Crossovers training on increasing dribbling ability in Syekh Yusuf football school athletes, as proven by an increase in speed from an average value of 23.5720 to 18.3890 with an observation value of 12.295 > ttable 2.262 and a significant value of 0.000 < α0.05; (3) There is a difference in the influence between Criscross training and Crossovers training on improving dribbling ability in football games in Syekh Yusuf football school athletes with a difference value of 16.3340 < 18.3890 with an observation value of 5.622 > ttable 2.101 and a significant value of 0.000 < α0.05. The conclusion is that Criscross training has a greater influence compared to Crossovers training on improving dribbling ability in football games in Syekh Yusuf football school athletes.